Prevalence of Overweight and Obesity in 7-9 Year-Old portuguese Children: Trends in Body Mass Index From 1970-2002 - Padez, C. (2009)
OBJECTIVE: The aim of this study was to analyse changes in the prevalence of overweight and obesity between 1986 and 2000 in Portuguese conscripts, and to examine the role of place of residence and educational level. STUDY DESIGN: Cross-sectional study. METHODS: Data sets from the cross-sectional annual surveys of all 18-year-old Portuguese males born between 1966 and 1981 and examined between 1986 and 2000 (850 081 subjects) were used in this study. Height and weight were measured and body mass index was calculated. Data on educational level (4, 6, 9, 11 and 12+ years) and residence (urban, semi-urban and rural) were collected. RESULTS: The prevalence of overweight increased from 10.5% in 1986 to 21.3% in 2000, and the prevalence of obesity increased from 0.9% to 4.2% in the same period (P<0.001). After adjustment for year of examination, the odds ratio (OR) for being overweight increased with educational level (reference 4-6 years: 1.19; 9 years: 1.30; 11 years: 1.47; 12+ years: 2.41) and place of residence (reference urban-semi-urban: 1.04; rural: 1.06). The prevalence of obesity increased with educational level (reference 4-6 years: 1.27; 9 years: 1.79; 11 years: 1.83; 12+ years: 2.66) and decreased with place of residence, i.e. those who lived in rural areas had a lower risk of becoming obese (OR: 0.94). CONCLUSIONS: Despite the low prevalence of obesity in young males in Portugal compared with other European countries, the sharp increase in recent years indicates that public health strategies are needed to prevent obesity.